Efeitos da hidroterapia e do posicionamento hammock no ganho de peso de recém-nascidos prematuros de baixo peso:um ensaio clínico randomizado - Justino, Jeferson de Sousa (2025)
Introduction: Premature newborns, particularly those with low birth weight, often experience delayed growth and development. Objective: To evaluate and compare whether hydrotherapy and hammock positioning techniques assist in the weight gain of premature newborns. Methodology: A singleblind andomized clinical trial was conducted at Santa Casa de Misericórdia Hospital in Sobral, between July 2022 and October 2023. The trial included 16 months of data collection and involved seventysix premature newborns with low birth weight, of which only sixty were included after meeting the inclusion criteria. These newborns were randomly divided into four groups each with 15 participants: one control group and three groups that received different intervention techniques (hydrotherapy, hammock positioning, and a combined group of hydrotherapy and hammock positioning). The newborns were monitored for clinical stability and specific signs before and after the interventions. The techniques were applied daily for 15 days. Results:During the 15-day follow-up, the control group had a mean weight gain of 305g. The group that received hydrotherapy gained 346g, but without statistical significance. The hammock group and the combined hydrotherapy and hammock group showed significant weight gains: the hammock group had an increase of 360g (p=0.011), while the combined group achieved a gain of 616g with p=0.0001. Significant increases in arm circumferences were observed only in the hammock group and the hydrotherapy combined with hammock positioning group. Conclusion: The results of the trial indicate that the combination of hydrotherapy and hammock positioning leads to a significant increase in weight gain in premature newborns. The isolated use of hammock positioning also showed positive effects, but the isolated use of hydrotherapy did not yield significant results. (Brazilian Registry of Clinical Trials (ReBEC) RBR-6g5f4jz).